PH, suhu air, dan perilaku pemberantasan sarang nyamuk terhadap keberadaan jentik nyamuk Aedes sp di Tembesi Lama, Kota Batam - Daswito, Rinaldi; Cahyadi, Najah Alya; Pitriyanti, Luh (TROPHICO: Tropical Public Health J., 2024)
Dengue hemorrhagic fever (DHF) is a disease caused by a virus spread by Aedes aegypti and Aedes albopictus mosquitoes that have been infected with the dengue virus. Dengue Hemorrhagic Fever (DHF) continues to be a health concern in Riau Islands Province, especially in Batam City. This study aimed to investigate the relationship between container condition and Eradication of Mosquito Den behavior (PSN) with the presence of larvae. A significant association was found between container type, water pH, container water temperature, and the existence of larvae in Tembesi Lama (p value <0.05). Location and container closing conditions variables were not statistically associated with the presence of larvae (p value >0.05). The study discovered that non-disposable containers within the house had the greatest number of Aedes sp. mosquito larvae. Additionally, mosquito larvae were identified in containers without a lid, with a water pH greater than 7.8, and a temperature between 27-30ËšC. When measuring PSN behavior, the majority of respondents in Tembesi Lama RT.01-02 RW. 02 had engaged in various PSN activities at their residences. Respondents have not effectively implemented certain PSN actions.